Necesidad o no del uso de colorantes durante la remoción de la dentina cariada: soporte microbiológico - Libbe Mariaca-de Botero; Gladys Martínez-Cifuentes; Patricia Rivas-Pulido; Beatriz Restrepo-Espinal (Universidad de Antioquia, 1998)
The complete dentinal cakes removal is a complex process, because the difficulty in define an objetive judgment in order to distinguish between infected and afected dentin. One way to reduce that subjectivity is using a caries detector dye. Nevertheless, there is a controversy about indications, advantages and disadvantages of this technique. This study compared the electiveness of a conventional tactile and optical criteria and the use of a caries detector dye (1% acid red in propylene glycol) in dentinal caries removal. The microbiological sampling of dye stained and dye unstained dentin were cuantify and classify in 34 patients who presented moderate tooth decay. The results of this investigation showed that 97% of the cavities after dentinal caries removal, showed dye stain more fecuently in the pulpal wall and the enamel - dentin junction. It is known that dyes stain carious dentin, sound circumpulpal dentine and enamel-dentin junction, and it's use could result in unnecesary sound dentin removal and several pulpal exposure. "Lactobacilli" and streptococcus "mutans" group comprised only 12.79% of the cultivable flora and 61.81% were not identify and their role in the porgression in dental cakes is unknown. It was not found correlation between the caries advanced front, decaloration and bacterial front.